Strategies to mitigate the emission of methane in pastures: enteric methane: A review - Siqueira, Juliana Silva [UNESP]; Vieira, Taynara Aparecida [UNESP]; Nakandakare-Maia, Erika Tiemi [UNESP]; Palacio, Thiago Luiz Novaga [UNESP]; Sarzi, Felipe [UNESP]; Garcia, Jessica Leite [UNESP]; Paula, Bruno Henrique de [UNESP]; Bazan, Silmeia Garcia Zanati [UNESP]; Baron, Giovanna; Tucci, Luigi; Janda, Elzbieta; Altomare, Alessandra; et al. (Southern Cross Publishing, 2022)
The global population reached 7.9 billion in 2021, which represents a 160% increase in the number of people to be fed since 1960. Agricultural systems must sustainably meet food demand for this growing population while minimizing or mitigating potential environmental impacts, which are of growing concern to both consumers and the scientific community. High protein animal products (meat and milk) play a crucial part in human nutrition and pastures represent ~20% of the planet’s surface. Pastoral areas have a great influence on both ecological balance and human subsistence. Ruminant livestock production systems are hotly debated because of the emission of methane, which is produced during enteric fermentation of ingested food within the rumen. Methanogenesis is a naturally occurring process in the digestive system of ruminant animals and ingesting a high-quality diet has been shown to reduce methane production. An additional function of pastoral grasslands is the capacity of the soils to operate as carbon sinks. Well managed pastures absorb carbon from the atmosphere where it can add to soil organic matter directly, through residue decomposition or excrement returns. However, in Brazil and globally, the efficiency of animal productivity tends to be lower in extensively grazed farming systems. Changes to pasture and grazing management in combination with the adoption of technology is necessary to improve the quality of pastures, increase animal productivity, and consequently reduce methane emissions from ruminant livestock. This review will discuss how to improve the conversion efficiency using pasture management to reduce or mitigate enteric methane production.
Keywords: Forage quality; Greenhouse gases; Pasture management.